2013
DOI: 10.5326/jaaha-ms-5829
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing Factors for Colonic Torsion/Volvulus in Dogs: A Retrospective Study of Six Cases (1992–2010)

Abstract: The purposes of this retrospective study were to review cases of colonic torsion/volvulus between July 1992 and August 2010 and to determine if any predisposing factors exist for the development of this condition. Six dogs were diagnosed with colonic torsion/volvulus during the study period. Four dogs had a history of previous gastric dilation-volvulus (GDV) with prophylactic gastropexy. Three of six dogs diagnosed with colonic torsion/volvulus had large intestinal entrapment and strangulation around the gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
41
3
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 11 publications
9
41
3
2
Order By: Relevance
“…The current study findings are in agreement with previous studies stating that colonic torsion is a rare condition, typically seen in adult, male, large breed dogs such as Great Danes, Labrador Retrievers, and German Shepherds . The reason for a higher incidence in males remains unknown .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current study findings are in agreement with previous studies stating that colonic torsion is a rare condition, typically seen in adult, male, large breed dogs such as Great Danes, Labrador Retrievers, and German Shepherds . The reason for a higher incidence in males remains unknown .…”
Section: Discussionsupporting
confidence: 93%
“…Other clinical signs such as diarrhea, tenesmus, and anorexia have also been reported . It has been suggested that dogs with prior history of gastrointestinal disease and/or abdominal surgery may be predisposed to developing colonic torsion …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenteric volvulus has no pathognomonic clinical signs, although the presentation often contains weakness, recumbency, abdominal pain and distension and shock in acute cases and also there may be a history of vomiting, diarrhea, hematemesis, or hematochezia that were in agreement with present case [7,8] .…”
Section: Discussionsupporting
confidence: 77%
“…Bacteria can be readily absorbed from the peritoneum and enter the systemic circulation. By the time these changes are present, lesions are irreversible and the prognosis is poor [3,8,9] . In addition, major tissue damage not only happens during the period of ischemia, but also when the ischemia is dismissed and the tissues are reperfused.…”
Section: Discussionmentioning
confidence: 99%